Perlindungan Hukum Merek di Jaringan Internet dalam Undang-undang Nomor 15 Tahun 2001 tentang Merek - Th Anita Cristiani (Fakultas Hukum Universitas Islam Indonesia, 2001)
The 2001 Trade Mark Acthas not arrangedabout trademarkprotection in cyberspace. Therefore it is important to form special regulation on trade mark protection in cyber space.